1979
DOI: 10.1029/jb084ib05p02223
|View full text |Cite
|
Sign up to set email alerts
|

A complete solution of a one‐dimensional propagating fault with nonuniform stress and strength

Abstract: We have investigated details of the dynamics of faults with strongly variable stress and frictional strength. These factors are in all likelihood responsible for nonuniform fault slip, multiple events, random ground acceleration, and the earthquake frequency‐magnitude relation. In order to obtain a full dynamic solution to greatly heterogeneous faulting we used a one‐dimensional continuum model in which stress and strength varied along the fault. The results show that the process of rupture in a heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The distribution of fault strength is also expected to contribute to the earthquake slip asymmetry. Prior works have suggested on a theoretical basis that earthquake slip distributions might be controlled by strength and stress variations along fault planes [e.g., Das and Aki , ; Nur , ; Israel and Nur , ; Madariaga , ; Bürgmann et al ., ; Boatwright and Cocco , ; Cooke , ; Noda and Lapusta , ; Kaneko et al ., ]. The reduction of on‐fault slip deficit at intersegments in the direction of greater maturity leads to longer fault segments in that direction (see Bohnhoff et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of fault strength is also expected to contribute to the earthquake slip asymmetry. Prior works have suggested on a theoretical basis that earthquake slip distributions might be controlled by strength and stress variations along fault planes [e.g., Das and Aki , ; Nur , ; Israel and Nur , ; Madariaga , ; Bürgmann et al ., ; Boatwright and Cocco , ; Cooke , ; Noda and Lapusta , ; Kaneko et al ., ]. The reduction of on‐fault slip deficit at intersegments in the direction of greater maturity leads to longer fault segments in that direction (see Bohnhoff et al .…”
Section: Discussionmentioning
confidence: 99%
“…Earthquake slip asymmetry is a generic feature, and therefore, our objective here is to identify the deterministic, generic factors that might control it. Slip heterogeneity may arise from heterogeneities of stress or material properties, including fault friction properties, fluid‐related fault zone properties, and elastic stiffness of the host rock [e.g., Nur , ; Israel and Nur , ; Madariaga , ; Bürgmann et al ., ]. Prior studies have shown that certain structural properties of faults affect significantly the properties of the earthquakes they host, such as their slip amplitude and rupture length [ Manighetti et al ., ], magnitude [ Anderson et al ., ], magnitude‐frequency distribution [ Stirling et al ., ], apparent stress drop [ Cao and Aki , ; Choy and Kirby , ; Manighetti et al ., ; Hecker et al ., ], number of broken segments [ Wesnousky , ; Manighetti et al ., ], and ground motion amplitudes [ Radiguet et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have also noticed the importance of heterogeneity and attempted to take it into their models (e.g. Dieterich 1972a; Knopoff, Mouton & Burridge 1973;Das & Aki 1977;Nur 1978;Israel & Nur 1979).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest therefore that seismic activity on the small individual fault planes, or asperity facets, on which these clusters of events occur is short-lived, existing for periods of the order of weeks or at most a few months. Theoretical studies (for example by Aki 1979 andIsrael andNur 1979) suggest that stress concentrates along a fault at barriers and asperities. Clusters, or families, of earthquakes with identical or near-identical seismograms (doublets) have been described from Japan (Tsujiura 1983) and the USA (Ishida and Kanamori 1980;Geller and Mueller 1980).…”
Section: 3 Clusters -Discussionmentioning
confidence: 99%